Acute bilateral retina hemorrhages beneath internal limiting membrane: An unusual ophthalmological case report of acute leukemia during complete clinical remission. Issue 7 (February 2018) - Lyu, Shuyuan; Zhang, Ming; Gao, Yunxia
Abstract: Rationale: Leukemia is a common hematologic disease that causes various systemic complications, such as ophthalmological disorders. The venous congestion is considered to be the main clinical sign that occurs during the initial stage of the disease, whereas white-centered hemorrhages are the most typical manifestations in leukemic retinopathy. These complications usually manifest when the disease presents with clinical and hematological symptoms. In the present study, we report a patient who was diagnosed with leukemic retinopathy. The initial signs of this disease were bilateral hemorrhages that occurred during complete clinical remission. Previous studies regarding this condition are quite rare. Patient concerns: We report a 26-year-old man who was diagnosed with leukemic retinopathy and exhibited the initial signs of the disease, namely bilateral hemorrhages with a distinct appearance beneath the internal limiting membrane. In addition, flame-shaped hemorrhages were observed surrounding the optic discs and/or along the vessels in the absence of venous congestion. All these changes were present during complete clinical remission. Diagnoses: Bilateral acute leukemic retinopathy, acute lymphoblastic leukemia (pro-B lymphocyte, BCR-ABL chimeric gene-positive). Interventions: Clinical remission was achieved following effective systemic chemotherapy that was applied for leukemia in the hematology department. A dynamic observation was applied actively in the absence of surgery and/or medical treatment for ophthalmologic treatment. Outcomes: Best corrected visual acuity was 20/40 in the right eye and 20/60 in the left eye, which was considerably better than those noted at the initial visit of the patient (20/250 in the right eye and 20/400 in the left eye). Lessons: The cautious expectant treatment is safe and helpful for acute leukemic retinopathy. A long-term follow-up is inevitable. Effective systemic chemotherapy that is required for leukemia treatment can achieve clinical remission, which might be helpful in controlling the pathological changes of the eyes.